APLIKASI PENCARIAN DATA OBAT MENGGUNAKAN ALGORITMA RABIN-KARP (STUDI KASUS : APOTEK SAMMULIA MEDIKA) - Yana Moerti; Sutardi Sutardi; Rahmat Ramadhan (semanTIK, 2018)
Currently, there is still a lot of writing / recording of data (drug) on conventional pharmacies done. One of them is the pharmacy Sammulia Medika. Medication data processing at pharmacy Sammulia Medika still use manual recording method, that is all data recorded in a book or archive, for that needed by drug data search application.The data search algorithm used is Rabin-Karp algorithm used to perform string searching process by using k-gram process for word distribution, and using hashing function to find pattern in text string and similarity that is similarity between words searched with existing word.Based on the results of the test, Rabin-Karp algorithm can be implemented in drug data search application to match word with similarity value up to 100%.Keywords—Drug Data, String Search, Rabin-Karp Algorithm. DOI : 10.5281/zenodo.1402396